ATAD3B is a mitophagy receptor mediating clearance of oxidative stress‐induced damaged mitochondrial DNA. (5th March 2021) - Shu, Li; Hu, Chao; Xu, Meng; Yu, Jianglong; He, He; Lin, Jie; Sha, Hongying; Lu, Bin; Engelender, Simone; Guan, Minxin; Song, Zhiyin
Abstract: Mitochondrial DNA (mtDNA) encodes several key components of respiratory chain complexes that produce cellular energy through oxidative phosphorylation. mtDNA is vulnerable to damage under various physiological stresses, especially oxidative stress. mtDNA damage leads to mitochondrial dysfunction, and dysfunctional mitochondria can be removed by mitophagy, an essential process in cellular homeostasis. However, how damaged mtDNA is selectively cleared from the cell, and how damaged mtDNA triggers mitophagy, remain mostly unknown. Here, we identified a novel mitophagy receptor, ATAD3B, which is specifically expressed in primates. ATAD3B contains a LIR motif that binds to LC3 and promotes oxidative stress‐induced mitophagy in a PINK1‐independent manner, thus promoting the clearance of damaged mtDNA induced by oxidative stress. Under normal conditions, ATAD3B hetero‐oligomerizes with ATAD3A, thus promoting the targeting of the C‐terminal region of ATAD3B to the mitochondrial intermembrane space. Oxidative stress‐induced mtDNA damage or mtDNA depletion reduces ATAD3B‐ATAD3A hetero‐oligomerization and leads to exposure of the ATAD3B C‐terminus at the mitochondrial outer membrane and subsequent recruitment of LC3 for initiating mitophagy. Furthermore, ATAD3B is little expressed in m.3243A > G mutated cells and MELAS patient fibroblasts showing endogenous oxidative stress, and ATAD3B re‐expression promotes the clearance of m.3243A > G mutated mtDNA. Our findings uncover a new pathway to selectively remove damaged mtDNA and reveal that increasing ATAD3B activity is a potential therapeutic approach for mitochondrial diseases. SYNOPSIS: The quality control machinery ensuring removal of damaged mitochondrial DNA (mtDNA) upon oxidative stress remains unclear. This work identifies mitochondrial protein ATAD3B as recruitment factor for LC3 to initiate PINK1/Parkin‐independent mitophagy and promote the clearance of damaged mtDNA in mammalian cells. ATAD3B is a novel regulator of oxidative stress‐induced mitophagy. Oxidative stress reduces ATAD3B‐ATAD3A hetero‐oligomerization and induces ATAD3B localization at the mitochondrial outer membrane. ATAD3B contains a LIR motif that binds to LC3 and initiates mitophagy in a PINK1‐independent manner. ATAD3B promotes the clearance of damaged mtDNA by mitophagy. Abstract : LIR motif‐containing protein ATAD3B recruits LC3 to mitochondria for PINK1/Parkin‐independent mitophagy in mammalian cells.